(untitled) (Conferencea, 2022)
The article is devoted to the study of cultural concepts in fictional prose. It reveals the hidden peripheral characteristics of the “Queen” concept which realizes linguocultural aspect of category of modality, analyzing examples from the works of these authors O. Wilde, G. Wells, O. Huxley